2019
DOI: 10.3390/data4040139
|View full text |Cite
|
Sign up to set email alerts
|

Korean Tourist Spot Multi-Modal Dataset for Deep Learning Applications

Abstract: Recently, deep learning-based methods for solving multi-modal tasks such as image captioning, multi-modal classification, and cross-modal retrieval have attracted much attention. To apply deep learning for such tasks, large amounts of data are needed for training. However, although there are several Korean single-modal datasets, there are not enough Korean multi-modal datasets. In this paper, we introduce a KTS (Korean tourist spot) dataset for Korean multi-modal deep-learning research. The KTS dataset has fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Our evaluation of forest fire smoke images revealed that vision-based systems had inadequacies in their datasets, and existing open-access datasets also had issues. To ensure that our learners were capable of detecting various sizes of forest fire smoke, we utilized forest fire smoke images [ 18 , 55 ], wildland images [ 56 ] for non-wildfire photos, and other web-based images. These datasets were obtained through crawling pictures or videos captured by a UAV, as the forest fire smoke model was developed to utilize the UAVs for monitoring purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Our evaluation of forest fire smoke images revealed that vision-based systems had inadequacies in their datasets, and existing open-access datasets also had issues. To ensure that our learners were capable of detecting various sizes of forest fire smoke, we utilized forest fire smoke images [ 18 , 55 ], wildland images [ 56 ] for non-wildfire photos, and other web-based images. These datasets were obtained through crawling pictures or videos captured by a UAV, as the forest fire smoke model was developed to utilize the UAVs for monitoring purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis of wildfire smoke detection datasets revealed that the datasets created for vision-based wildfire smoke detection systems were deficient and that existing open-access datasets had their own set of problems. Existing wildfire UAV images [ 66 ], a Korean tourist spot database [ 67 ] for non-wildfire mountain images, and the Kaggle, Bing, Google, and Flickr images were used to address these concerns. Both datasets were crawled from images or videos obtained using a drone, as the early wildfire smoke detection model is meant for applications in drones and UAVs for monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis of forest fire smoke images has brought to light shortcomings in datasets used by vision-based systems, and existing open-access datasets have also demonstrated deficiencies. To empower our learning systems to discern various extents of forest fire smoke, we harnessed forest fire smoke images [10,52,53], along with wildland images [54] for non-wildfire scenarios, and augmented these with images sourced from the web. These datasets were acquired through the collection of pictures or videos taken by UAVs, aligning with the development of the forest fire smoke model optimized for UAV-based monitoring applications.…”
Section: Forest Fire Smoke Dataset Collectionmentioning
confidence: 99%